The importance of using movies in EFL classrooms - Daraselia, Maya; Jojua, Tamar (The International tax journal, 2024)
To improve EFL learners’ language skills, it is approved to integrate movies in the teaching/learning, systematically using words, phrases and different speech patterns learned from movies in communicative situations . All the techniques for working with movies and TV shows are fun and effective. However, while such training is enjoyable, it takes time, patience, effort and reasonable approaches.